2020
DOI: 10.1111/mmi.14525
|View full text |Cite
|
Sign up to set email alerts
|

In situ structure of the Caulobacter crescentus flagellar motor and visualization of binding of a CheY‐homolog

Abstract: Bacterial flagella are propulsive helical filaments rotated by intricate nanomachines for motility, which quickly respond to environmental conditions by binding various effector proteins. Effector binding facilitates effective swimming motility, swarming motility (Jarrell and McBride, 2008) and surface sensing in the early phases of biofilm formation (Hug et al., 2017; Laventie et al., 2019). The mechanistic core of these motors is a "gearbox" that drives and modulates flagellar rotation, composed of a rotatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Second, density similar in location and shape has been shown two recent studies to be CheY-P. Chang et al have used GFP-tagged CheY-P to show that, in Borrelia burgdorferi , CheY-P occupies the same position ( Chang et al, 2020 ). Rossmann et al also identified similar density for the CheY homolog, CleD in Caulobacter crescentus ( Rossmann et al, 2020 ). Third, when we place the crystal structure of CheY into the model, there is about 60 Å gap between the C-ring density and this additional density ( Figure 3—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 83%
“…Second, density similar in location and shape has been shown two recent studies to be CheY-P. Chang et al have used GFP-tagged CheY-P to show that, in Borrelia burgdorferi , CheY-P occupies the same position ( Chang et al, 2020 ). Rossmann et al also identified similar density for the CheY homolog, CleD in Caulobacter crescentus ( Rossmann et al, 2020 ). Third, when we place the crystal structure of CheY into the model, there is about 60 Å gap between the C-ring density and this additional density ( Figure 3—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 83%
“…It was recently shown that the chemotaxis response regulator CheY interacts with the C‐ring of fully assembled flagella, forming an associated ring ~ 50 nm in diameter that locks the switch complex in clockwise direction by interacting with the C‐ring protein FliM (Carroll et al , 2020; Chang et al , 2020; Rossmann et al , 2020). While superficially similar, the novel rings we discovered assemble before FliM and even in its absence (in ∆ fliM fliP* H. pylori ), indicating that they are of a different nature.…”
Section: Discussionmentioning
confidence: 99%
“…By performing subtomogram averaging on the identified PL-subcomplexes, we found that they contain, in addition to the P-and L-rings, two other periplasmic rings known as the outer membrane (OM) ring and the cogwheel (Fig. 1J), which are also present in the fully-assembled motor of C. crescentus 12 . These two rings were not visible in the PL-subcomplex previously reported on the poles of swarmer cells due to the low number of particles identified at the time 3 .…”
mentioning
confidence: 99%